La rénovation énergétique des bâtiments en France entre marché, actions territoriales et dispositions nationales - Gilles Debizet (Développement Durable et Territoires)
In France, the “Grenelle de l’Environnement” stakeholders agreed and planned on using thermal renovation on private buildings to reduce greenhouse gas emissions. They reached an agreement even though the cost was estimated as hundreds of billion euros. Its implementation is actually more difficult than expected: in the absence of the obligation to renovate, really hard to legally set up, public initiatives are required. The OPATB experience shows how slow this innovative process is and how important it is to support financially decision-makers and advise them especially for building co-owners. To locally articulate informative mission and support with a national tax fare system, requires agreements at a local and national level, which will probably take years to happen.